POTENTIAL DRIVER FOR ACCELERATING ADIABATIC DYNAMICS IN COMPLEX WAVE FUNCTIONS - Nurhasanah; Setiawan; D Hamdan (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2023)
This research is a theoretical study that investigates the literature reviewing the adiabatic acceleration methods of quantum particle dynamics through the application of the fast forward method. This method was initially developed by Masuda and Nakamura in 2010. In this approach, the acceleration scheme is generated through the modification of the Hamiltonian by including regularization terms in the original Hamiltonian. In this study, the fast forward method is applied to a harmonic oscillator system. The fast forward method is first employed to obtain the adiabatic phase. In the subsequent step, through a review of the system's states, a driving potential is identified that ensures the harmonic oscillator system can transition from the initial state to the final state in a short period of time while preserving the system's energy. This research employs adiabatic parameters that are of a general nature, allowing for the use of freely selectable parameters.